Effects of thread interruptions on tool pins in friction stir welding of AA6061. (17th February 2018) - Reza-E-Rabby, Md.; Tang, Wei; Reynolds, Anthony P.
ABSTRACT: In this work, effects of pin thread and thread interruptions (flats) on weld quality and process response parameters during friction stir welding (FSW) of 6061 aluminium alloy were quantified. Otherwise, identical smooth and threaded pins with zero to four flats were adopted for FSW. Weldability and process response variables were examined. Results showed that threads with flats significantly improved weld quality and reduced in-plane forces. A three-flat threaded pin led to production of defect-free welds under all examined welding conditions. Spectral analyses of in-plane forces and weld cross-sectional analysis were performed to establish correlation among pin flats, force dynamics and defect formation. The lowest in-plane force spectra amplitudes were consistently observed for defect-free welds.